Slezavit as a Component of Neuroprotective Therapy for Primary Open-Angle Glaucoma (Eurasian Medical Research Periodical, 2022)
The term "glaucoma" unites a large group of eye diseases of various origins with a progradient, chronic course. As a rule, glaucoma occurs with an increase in the level of intraocular pressure (IOP; with the exception of glaucoma with the so-called low (pseudonormal) pressure), the development of optic neuropathy, which is manifested by characteristic changes in the retinal fibers of the retina of the optic nerve head, and progressively worsening visual functions with the appearance of typical visual field defects